Therapeutic Performance Evaluation of 213Bi-Labelled Aminopeptidase N (APN/CD13)-Affine NGR-Motif ([213Bi]Bi-DOTAGA-cKNGRE) in Experimental Tumour Model: A Treasured Tailor for Oncology - Zita Képes; Viktória Arató; Judit P. Szabó; Barbara Gyuricza; Dániel Szücs; István Hajdu; Anikó Fekete; Frank Bruchertseifer; Dezső Szikra; György Trencsényi (Pharmaceutics, 2023)
Since NGR-tripeptides (asparagine-glycine-arginine) selectively target neoangiogenesis-associated Aminopeptidase N (APN/CD13) on cancer cells, we aimed to evaluate the in vivo tumour targeting capability of radiolabelled, NGR-containing, ANP/CD13-selective [213Bi]Bi-DOTAGA-cKNGRE in CD13pos. HT1080 fibrosarcoma-bearing severe combined immunodeficient CB17 mice. 10 ± 1 days after cancer cell inoculation, positron emission tomography (PET) was performed applying [68Ga]Ga-DOTAGA-cKNGRE for tumour verification. On the 7th, 8th, 10th and 12th days the treated group of tumourous mice were intraperitoneally administered with 4.68 ± 0.10 MBq [213Bi]Bi-DOTAGA-cKNGRE, while the untreated tumour-bearing animals received 150 μL saline solution. In addition to body weight (BW) and tumour volume measurements, ex vivo biodistribution studies were conducted 30 and 90 min postinjection (pi.). The following quantitative standardised uptake values (SUV) confirmed the detectability of the HT1080 tumours: SUVmean and SUVmax: 0.37 ± 0.09 and 0.86 ± 0.14, respectively. Although no significant difference (p ≤ 0.05) was encountered between the BW of the treated and untreated mice, their tumour volumes measured on the 9th, 10th and 12th days differed significantly (p ≤ 0.01). Relatively higher [213Bi]Bi-DOTAGA-cKNGRE accumulation of the HT1080 neoplasms (%ID/g: 0.80 ± 0.16) compared with the other organs at 90 min time point yields better tumour-to-background ratios. Therefore, the therapeutic application of APN/CD13-affine [213Bi]Bi-DOTAGA- cKNGRE seems to be promising in receptor-positive fibrosarcoma treatment.